Divide, Provide and Rule : An Integrative History of Poverty Policy, Social Reform, and Social Policy in Hungary under the Habsburg Monarchy - Zimmermann, Susan (Book collections on Project MUSE., 2011)
A concise and comprehensive account of the transformation of social policy from traditional poor relief towards social insurance systems in a European state before World War One. Brings together the analysis of older, mostly local welfare policies with the history of social policy developed by the state and operated at a national level. Explores also the interaction of various layers of and actors in welfare policy, i.e. of poor relief, social reform policies and the unfolding welfare state over time, including often neglected elements of these policies such as e.g. protective policies at the work place, housing policy, child protection, and prostitution policies.